Dziecko w działaniu – refleksje praktyka - Paulina Grzelecka (Problemy Wczesnej Edukacji)
Being a refl ective practitioner is a task for a teacher and a tool for his real professional development. This article presents a teacher’s refl ection before action, focused on the goal of education, a refl ection in action, where the teacher is an observer, tutor and diagnostician, and a refl ection after action, where I analyzed children’s activity in classes with educational toys. For the teacher’s work I have described the possibility of diagnosing students cognitive development based on their social role; how do they build strategies of logical thinking; what is wrong with preschool education; and how to engage students in classes. This text is a result of taking a part in the project Laboratorium Wczesnej Edukacji.